Edukasi Penerapan Protokol Kesehatan dalam Upaya Pencegahan Penularan Covid-19 di Kelurahan Pantoloan : Education on the Implementation of Health Protocols in Efforts to Prevent the Transmission of Covid-19 in the Pantoloan Village - Lisnawati, Lisnawati; Zainul, Zainul; Muliani, Muliani; Hafid, Fahmi; Taqwin, Taqwin (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2023)
Introduction: In 2021 there were 22,403 positive confirmed cases of Covid-19 in Central Sulawesi, 595 cases died, and 5,992 people underwent quarantine. The number who have confirmed positive in Palu City is 4,993 people. One of the areas at high risk of an increase in cases in Palu City is Pantoloan Village, which is a port area where passengers come and go from various regions. Health cadres and related organizations need to be empowered to increase socialization of the implementation of health protocols in the community to prevent Covid-19. Community service program activities by lecturers at the Poltekkes Kemenkes Palu aim to provide understanding to the public about the application of health protocols in an effort to prevent the transmission of Covid-19 in the Pantoloan Village. The methods of this activity is carried out by providing counseling and education to implement health protocols so that the transmission of Covid-19 can be prevented with infocus media. Implementation of activities on July 12-13 2022. Participants in this activity totaled 30 people consisting of PKK cadres and mothers. The results show an increase in knowledge from the pre and post test with an average score of 60.80 to an average of 80.90. Suggestions for PKK cadres and women who have been educated together with the local government and community leaders to actively carry out health socialization or promotion related to the implementation of correct and routine health protocols, especially in the Pantoloan Village. For related agencies, it is necessary to educate the public regarding the spread of Covid-19, especially in areas prone to spread, such as in port and border areas.